(untitled) (Sport Science Research, 2024)
Despite the great popularity of Greco-Roman style wrestling and the success of Kazakhstan athletes in the international sports arena, there is no in-depth analysis of the competitive performance of our athletes at major sports competitions in the literature available to us. The purpose of the study was to analyze the performances of Kazakhstan Greco-Roman wrestlers at major international competitions. Such research methods as analysis of literary sources, analysis of protocols of performances of Kazakhstan athletes at international competitions, analysis of profiles of Kazakhstan athletes in the International Wrestling Database were used. Analyzing the performances of Kazakhstan Greco-Roman wrestlers at such major international competitions as the World Cup and the Olympic Games, we can conclude that their competitive performance has decreased. In recent years, the share of gold medals in the medal standings of the national team has decreased and the share of bronze medals has increased. Kazakhstan Greco-Roman wrestlers are one of the regular participants of major international sports competitions. During the entire period of participation, Kazakhstan athletes at international competitions have won 12 medals of the European Championship, 43 medals of the World Championship and 16 medals of the Olympic Games. However, in recent years there has been a decrease in the competitive effectiveness of our athletes at major international competitions, including the Olympic Games.